ALIH FUNGSI LAHAN PADI MENJADI KARET DI DAERAH IRIGASI WAY RAREM PULUNG KENCANA KABUPATEN TULANG BAWANG BARAT - Sari, Anisa Maya; Ismono, R Hanung; Kasymir, Eka (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2015)
This research aims to determine the factors that affect the paddy converted land of the rubber plant, the economic value of the land (land rent) and welfare of farmers whose paddy fields converted into rubber plant functions. This research was conducted at the Regional Irrigation Way Rarem Pulung Kencana West Tulang Bawang regency. Data were taken from March to April 2015. The sampling technique is done with Simple Random Sampling Method. The sample consisted of 54 people consisting of farmers in the district Tulang Bawang Tengah are 27 samples, farmers in Sub Tumijajar are 15 samples, and farmers in District Tulang Bawang Udik are 12 samples. Data analized with multiple linear regression, revenue analysis, and to determine the level of welfare of farmers based on criteria of Sajogyo and the Central Bureau of Statistics. The results showed that (1) the factors that affect the paddy converted land into rubber plant functions at the Regional Irrigation Way Rarem Pulung Kencana West Tulang Bawang is the area of ​​land and the percentage of irrigated paddy field throughout the year, (2) the economic value of the land (land rent) farming rubber 2.85 times larger than the land rent paddy rice farming, (3) based on the criteria Sajogyo (1997), 87,04 percent of respondents are categorized quite prosperous, while based on the criteria of the Central Bureau of Statistics (2007), all the farmers’ respondents are belong to prosperous category. Key words: factors, converted land, land rent, welfare